Effects of different levels of Brachiaria decumbens diets on in vitro gas production and ruminal fermentation - Jaapar, Mimi Syazwani; Lim, Eric Teik Chung; Nayan, Nazri; Kamalludin, Mamat Hamidi; Saminathan, Mookiah; Muniandy, Kalai Vaani; Mohd Hamdan, Muhammad Hazziq; Jusoh, Shokri; Abdullah, Faez Firdaus Jesse (Nexus Academic Publishers, 2022)
Although B. decumbens is abundant in the tropics, the utilization of this grass is limited due to the presence of steroidal saponins. Therefore, the main objective of this study was to determine the effects of different levels of B. decumbens diets on the in vitro gas production and ruminal fermentation characteristics. Graded levels of B. decumbens were mixed with P. purpureum, where 10% was identified as the low-level B. decumbens diet (T2) and, 60% was identified as the high-level B. decumbens diet (T3) based on the concentration of saponins. Meanwhile, 100% P. purpureum was used as the basal diet, which served as control (T1). Rumen fluid was then collected from six young male Dorper cross sheep for the analyses of gas production, pH, in vitro organic matter digestibility, ammonia nitrogen, and volatile fatty acids (VFA). All analyses were conducted according to established methods and data collected were subjected to one-way analysis of variance (ANOVA) and Duncan’s Multiple Range Test to determine the level of significance among treatments. The net gas production and gas production kinetics demonstrated notable changes (P < 0.05) among treatments. Besides, only the acetic acid and total VFA showed significant differences (P < 0.05) for the rumen fermentation characteristics. Generally, the T3 diet consisted of 60% B. decumbens diet demonstrated the lowest gas production, gas production parameters, acetic acid, and total VFA concentrations as compared to the other treatments. In conclusion, 10% of B. decumbens mixture displayed minimal effects in the in vitro assessment, while 60% of B. decumbens mixture showed the most significant results out of all three treatments indicating the presence of saponins did influence negatively on the gas production and ruminal fermentation characteristics.